500 art quilts : an inspiring collection of contemporary work - Hemachandra, Ray.; Hale, Julie (New York, NY : Lark Books, 2010)
A collection of 500 international art quilts.
Introduction / by Karey Bresenhan -- The quilts -- About the juror -- Acknowledgments -- Contributing artists.
Includes index.
Keywords: Art quilts -- History -- 21st century